Prevalence of overweight, obesity and associated factors in preschoolers in the canton of Turrialba - Barrantes Montoya, Azálea; Calderón Rodríguez, Ashley; Fernández Rojas, Xinia (Población y Salud en Mesoamérica, 2017)
The objective of the present study was the analysis of the prevalence of overweight and obesity in preschool children intervened by the Póngale Vida Model in 2013, in the canton of Turrialba, Costa Rica. Population: 643 preschoolers from public institutions in Turrialba (2013). The educational system consists of two cycles for preschool: Maternal and Infant and Transition. Anthropometric data were collected at each school by teachers trained staff ‘Póngale Vida’ (2013). Anthropometric status was evaluated according to the criteria of the World Health Organization (WHO) 2008. The prevalence of excessive weight (overweight and obesity), was 18%, which is lower than reported by the National Nutrition Survey 2008-2009 (NNS) Costa Rica (21,4% (Ministry of Health of Costa Rica, 2009). Underweight was 8%, which is higher than the nationally reported by NNS 6.1% (Ministry of Health of Costa Rica, 2009). 94% of preschool children have normal height. Rural area (5%) had lower prevalence of underweight compared to urban areas (8%); overweight was similar. Higher percentage of underweight and overweight is observed among girls (9% and 19%) than in boys (6% and 16% respectively). In the range from 5 years to 6 years and 9 months (cycle Transition), occurred 87.5% of the cases of underweight, 93% of the ones of overweight and all cases (100%) of obesity. The frequency of breakfast, snack and dinner, the transportation medium, the playing hours and watching TV may influence nutritional status. Conclusion: There are differences in data regionally and nationwide of excess weight and associated factors. Further studies are recommended.